PENGARUH INVESTASI DAN PEMBANGUNAN MANUSIA DALAM PENGENTASAN KEMISKINAN DI INDONESIA - Dimas Bayu Nur Irvanie; Jihad Lukis Panjawa (Center for Economic Studies Universitas Katolik Parahyangan, 2023)
This study aims to examine the short-term and long-term effects of foreign direct investment, human development, economic growth, and electricity infrastructure on poverty alleviation efforts, which are proxied by the number of poor people below the national poverty line in Indonesia. The data used are time series data from 1996 to 2019, the methods used are Auto Regressive Distributed Lag (ARDL) and Error Correction Model (ECM) or ARDL-ECM. The results of this study indicate that in the short term foreign direct investment and human development index variables have a significant negative effect on poverty. And in the long term, only the electricity infrastructure variable has a significant negative effect on poverty in Indonesia. Meanwhile, the economic growth variable does not have a significant effect, either in the short or long term, on poverty in Indonesia.